Israel at war: an overview of the situation inside the country. (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2023)
This report delves into the current socio-political landscape in Israel, shedding light on the growing opposition to government reforms and heightened tensions during the formation of the new government. It explores the temporary pause in internal debates following the October 7, 2023, Hamas attack, with an expectation that these discussions will resume post-conflict. The primary focus is on depicting Israeli society and politics before the war and analysing the key elements that have defined its recent history.
Keywords: Israel; Netanyahu; Judicial Overhaul; Zionism; Protest